Changing prevalence and resistance patterns in children with drug-resistant tuberculosis in Mumbai. (3rd April 2017) - Shah, Ira; Shah, Forum
Abstract : Background: The prevalence of drug-resistant (DR) tuberculosis (TB) in children is increasing. Although, in India, multi-drug-resistant (MDR) TB rates have been relatively stable, the number of children with pre-extensively drug-resistant and extensively drug-resistant (XDR) TB is increasing. Aim: To determine whether the prevalence of DR TB in children in Mumbai is changing and to study the evolving patterns of resistance. Methods: A retrospective study was undertaken in 1311 paediatric patients referred between April 2007 and March 2013 to the Paediatric TB clinic at B. J. Wadia Hospital for Children, Mumbai. Children were defined as having DR TB on the basis of drug susceptibility testing (DST) of Mycobacterium tuberculosis grown on culture of body fluids (in the case of extra pulmonary TB) or from gastric lavage/bronchi-alveolar lavage/sputum in patients with pulmonary TB or from DST of the contacts. The prevalence of DR TB was calculated and the type of DR was evaluated yearly and in the pre-2010 and post-2010 eras. Results: The overall prevalence of DR TB was 86 (6.6%) with an increase from 23 (5.6%) patients pre-2010 to 63 (7%) post-2010 ( P   =  0.40). Nine (10.4%) patients were diagnosed on the basis of contact with a parent with DR TB. Overall fluoroquinolone resistance increased from 9 (39.1%) pre-2010 to 59 (93.7%) post-2010 ( P   =  0.0001): moxifloxacin resistance increased from 2 (8.7%) to 29 (46%) ( P   =  0.0018) and ofloxacin resistance increased from 7 (30.4%) to 30 (47.6%) ( P   =  0.14). Ethionamide resistance also increased from 6 (26.1%) to 31 (49.2%) ( P   =  0.04), aminoglycoside resistance was one (4.3%) pre-2010 and 12 (19%) post-2010 ( P   =  0.17) and resistance remained virtually the same for both amikacin [0 pre-2010 and 6 (9.5%) after 2010] and kanamycin [one (4.3%) pre- and 6 (9.5%) post-2010]. Of the first-line drugs, resistance remained the same for isoniazid [23 (100%) to 61 (96.8%)], rifampicin [22 (95.7%) to 51 (80.9%), P   =  0.17], pyrazinamide [15 (65.2%) to 35 (55.6%), P   =  0.47], ethambutol [14 (60.9%) to 38 (60.3%), P   =  1.00] and streptomycin [19 (82.6%) to 50 (79.4%), P   =  1.00]. Resistance to PAS remained unchanged [2 (8.7%) to 5 (7.9%), P   =  1.00]. Conclusion: There is increasing resistance to second-line anti-tuberculosis (ATT) drugs, particularly flouroquinolones and ethionamide. Hence, there is an urgent need to avoid the use of ATT drugs for non-tuberculous infection and to increase surveillance for DR TB in adults as MDR TB in children is usually through contact with an adult with infectious MDR TB.